PENDIDIKAN KARAKTER DALAM MEMBANGUN MODERASI BERAGAMA DI MADRASAH DINIYAH MUADALAH TSANAWIYAH NURUL QARNAIN JEMBER - Khoir, Qoidul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research discusses the implementation of character education in building religious moderation. The aim of this research is to provide an overview of how character education is applied in building religious moderation at Madrasah Muadalah Tsanawiyah Nurul Qarnain Jember. Apart from that, it is hoped that this research can provide useful information about the implementation of character education in building religious moderation in madrasas. The research location was chosen at Madrasah Muadalah Tsanawiyah Nurul Qarnain, because this institution is a formal educational institution that applies typical Islamic boarding school-based learning methods with the advantage of learning based on the yellow book (religious studies). This research method was carried out qualitatively with a descriptive approach, while data was collected through observation, interviews and documentation. The interview process carried out as supporting data for research at the Madrasah Muadalah Tsanawiyah Nurul Qarnain educational institution included several objects including: teachers, students and staff, as well as stakeholders involved in the formation of character education in building religious moderation. The research results show that character education is an important effort to teach students to make wise choices by applying the knowledge they have in everyday life. Students at Madrasah Muadalah Tsanawiyah Nurul Qarnain show a positive level of religious moderation. This is formed through the implementation of character education, including understanding religious knowledge, attitudes of tolerance, mutual respect, and awareness of religious diversity and religious perspectives. By implementing religious activities as a form of character education, Madrasah Muadalah Tsanawiyah Nurul Qarnain has succeeded in growing and increasing students' religiosity, in this case students show a positive level of religious moderation. Implementing character education through religious activities can help students develop strong and moderate religious attitudes.